Whole-of-nation Moral Learning by Spiritual Hearts: A Case of Brunei’s Evolving Education System - Haji Tarip, Mohammad Iznan; Abu Bakar, Nur Firdaus; Ash’ari, Zuraihi; Zulkifli, Fatin; Marsidi, Muzhafar (ADDIN, 2021)
The role of the spiritual heart in transformation and reformation is vital. However, the dynamism of change emanating from the heart is less understood. Using the work of al-Ghazālī (d. 505/1111), this paper centralises the noetic of the spiritual heart and its roles as a learning medium and a change agent. The heart is then conceptually operationalised within the national settings, particularly its role in whole-of-nation moral learning. This is further illustrated by a whole-of-nation moral learning trajectory situated within Brunei’s governance context, which is the (re)Islamisation of the national education system during three periods: pre-independence 1984, post-independence, and the new norm. The case showed the important roles of virtuous leaders to push for moral changes, followers to also engage in moral learning to suppress immoral learning, structures and cultures to be institutionalised to perpetuate moral learning, and selective international relations to catapult local progress.